Prevalence and determinants of diarrhea morbidity among under five children of west Shoa Zone, Oromia Region, Ethiopia - Bizunesh Kefale Mengistu; Girma Teferi Mengistu; Alemayehu Siffir Argawu; Dechasa Badada Tolessa; Emebet Chimdi (International Journal of Africa Nursing Sciences, 2024)
Background: Diarrhea is the leading cause of morbidity and mortality among under-five children, including Ethiopia. This study aimed to assess the prevalence and determinants of diarrhea morbidity among under-five children in the west Shewa zone. Methods: The community-based cross-sectional study was conducted using an interviewer-administered questionnaire. The study was conducted among 1004 study participants with under five children. The relation of covariates and diarrheal disease was checked using logistic regression at 95 %CI, where variables with p < 0.05 were statistically significant. Results: The finding revealed that the two-week prevalence of diarrhea in the west Shewa zone was 18.7 %. Children living in Ambo [AOR = 0.492, 95 %CI (0.255, 0.948)], Dendi [AOR = 0.413, 95 %CI (0.222, 0.769)], Toke kutaye [AOR = 0.462, 95 %CI (0.240, 0.889)], Bako Tibe [AOR = 0.522, 95 %CI (0.275, 0.993)] were less likely affected by diarrhea. Feeding by cup and spoon [AOR = 0.656, 95 %CI (0.433, 0.995)] and feeding by bottle [AOR = 0.577, 95 %CI (0.362, 0.922)] were less likely affected by diarrhea. Using untreated water [AOR = 1.795, 95 %CI (1.184, 2.721)], complementary feeding before six months [AOR = 1.798, 95 %CI (1.261, 2.565)], improper waste disposal [AOR = 2.041, 95 %CI (1.394, 2.989)], unvaccinated for rotavirus [AOR = 1.990, 95 %CI (1.162, 3.410)] were more likely develop diarrhea. Conclusion: Our study identified that one in five under-five children was affected by diarrheal morbidity. It was determined by the woreda of respondents, drinking water, child feeding method, complementary feeding initiation time, waste disposal, and rotavirus vaccination. All concerned bodies should intervene based on the cause of the disease.